The Influence of Teaching Readiness and Student Learning Motivation on Student Learning Outcomes in Class VII Social Studies Darma Pertiwi Junior High Scholl Bahbutong Sidamanik - Swantika Tri Ledis Purba; Binsar Tison Gultom; Benjamin Albert Simamora (Indonesian Journal of Advanced Research, 2023)
This research aims to determine the effect of teacher readiness and student learning motivation on student learning outcomes in Social Studies Class VII Darma Pertiwi Junior High Scholl Bahbutong. The type of research used in this study is quantitative research with an associative approach to the research design using a survey design. The population in this study were all students of class VII SMP Darma Pertiwi Bahbutong Sidamanik totaling 82 students. The sample in this study were 82 students. The sampling technique used the total sample technique, namely the number of samples is equal to the total population. The data collection techniques used observation techniques, interviews, documentation, and questionnaires. The data in this study were analyzed by the normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple regression analysis, t test, F test, and the coefficient of determination test. The results showed that there was an effect of teacher readiness on social studies learning outcomes of students with tcount > ttable (2.233 > 1.990). Furthermore, there was an influence of student learning motivation on student social studies learning outcomes with tcount > ttable (2,609 > 1,990). and there was an influence between teacher readiness to teach and student learning motivation on student social studies learning outcomes with Fcount > Ftable (3,783 > 3,111).